Emerging trends: A tribute to Charles Wayne. (9th October 2017) - CHURCH, KENNETH WARD
Abstract: Charles Wayne restarted funding in speech and language in the mid-1980s after a funding winter brought on by Pierce's glamour-and-deceit criticisms in the ALPAC report and 'Whither Speech Recognition'. Wayne introduced a new glamour-and-deceit-proof idea, an emphasis on evaluation. No other sort of program could have been funded at the time, at least in America. One could argue that Wayne has been so successful that the program no longer needs him to continue on. These days, shared tasks and leaderboards have become common place in speech and language (and vision and machine learning) research. That said, I am concerned that the community may not appreciate what it has got until it's gone. Wayne has been doing much more than merely running competitions, but he did what he did in such a subtle Columbo-like way. Going forward, government funding is being eclipsed by consumer markets. Those of us with research to sell need to find more and more ways to be relevant to potential sponsors given this new world order.